2018
DOI: 10.1016/j.celrep.2018.09.076
|View full text |Cite
|
Sign up to set email alerts
|

Human Huntington’s Disease iPSC-Derived Cortical Neurons Display Altered Transcriptomics, Morphology, and Maturation

Abstract: Highlights d Differentiated HD and non-diseased iPSCs into functional cortical neurons d HD iPSC-derived cortical neurons display altered transcriptomics d HD iPSC-derived cortical neurons display altered morphology d HD iPSC-derived cortical neurons display altered functional phenotypes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
81
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 69 publications
(87 reference statements)
9
81
0
3
Order By: Relevance
“…The published RNA-seq data of three cortical sub-regions (dorsolateral prefrontal cortex, ventrolateral prefrontal cortex, and orbital frontal cortex) at nine developmental stages (8,12,13,16,17,21,24, and 37 pcw and 4 months) of human brains were obtained from Allen Brain Atlas (http://www.brainspan.org/static/download.html). This dataset was compared with the organoids RNA-seq data of the current study to assess the degree of transcriptome correlation.…”
Section: Correlation Of Transcriptome Between Organoids and Human Bramentioning
confidence: 99%
See 3 more Smart Citations
“…The published RNA-seq data of three cortical sub-regions (dorsolateral prefrontal cortex, ventrolateral prefrontal cortex, and orbital frontal cortex) at nine developmental stages (8,12,13,16,17,21,24, and 37 pcw and 4 months) of human brains were obtained from Allen Brain Atlas (http://www.brainspan.org/static/download.html). This dataset was compared with the organoids RNA-seq data of the current study to assess the degree of transcriptome correlation.…”
Section: Correlation Of Transcriptome Between Organoids and Human Bramentioning
confidence: 99%
“…Indeed, studies examining neurogenesis using mouse HD stem cells have given conflicting results showing that mutant HTT both impairs neurogenesis [21] and promotes it [13,22]. Efforts to examine the impact of mutant HTT on neurodevelopment and neurogenesis using human pluripotent stem cells (hPSCs) having been similarly unclear [18,19,[23][24][25][26] (reviewed in [27]). Mutant HTT was shown to impact early ectodermal development, reflected in an altered phenotypic signature, in an in vitro model of neurulation [28].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…iPSC differentiation and treatment iPSC generation was previously performed at Cedar's Sinai Medical Center using nonintegrating methods (HD iPSC Consortium, 2012;Mattis et al, 2015;Mehta et al, 2018). These iPSCs were fully reprogrammed as previously demonstrated by testing for pluripotency markers and gene expression analysis (Mattis et al, 2015), and removal of reprogramming plasmids was confirmed by genomic polymerase chain reaction (PCR) and southern blotting (Mattis et al, 2015).…”
Section: Mouse Striatal Western Blotmentioning
confidence: 99%